Consumption Resources and Self-Creation Process: A Key Resource and Multi-Component Resource Perspective - Wattanasuwan, Kritsadarat; ฺBoonchoo Pattana; Lertwannawit, Aurathai (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2022)
Based on the key resource and multiple-component resource theories, we propose a conceptual model to substantiate the relations among consumer experiences, symbolic consumption, and self-expression. Our first proposition posits that consumer experiences, both lived and mediated, have an impact on the appropriation of symbolic consumption, which could take the form of self- and/or social symbolism. Our second proposition posits that symbolic consumption affects consumers’ self-expression. The model can be a theoretical framework for future empirical studies. We conclude this paper with a discussion of our theoretical and managerial contributions.